8x-(6x+5)=3x-33

Simple and best practice solution for 8x-(6x+5)=3x-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(6x+5)=3x-33 equation:


Simplifying
8x + -1(6x + 5) = 3x + -33

Reorder the terms:
8x + -1(5 + 6x) = 3x + -33
8x + (5 * -1 + 6x * -1) = 3x + -33
8x + (-5 + -6x) = 3x + -33

Reorder the terms:
-5 + 8x + -6x = 3x + -33

Combine like terms: 8x + -6x = 2x
-5 + 2x = 3x + -33

Reorder the terms:
-5 + 2x = -33 + 3x

Solving
-5 + 2x = -33 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-5 + 2x + -3x = -33 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-5 + -1x = -33 + 3x + -3x

Combine like terms: 3x + -3x = 0
-5 + -1x = -33 + 0
-5 + -1x = -33

Add '5' to each side of the equation.
-5 + 5 + -1x = -33 + 5

Combine like terms: -5 + 5 = 0
0 + -1x = -33 + 5
-1x = -33 + 5

Combine like terms: -33 + 5 = -28
-1x = -28

Divide each side by '-1'.
x = 28

Simplifying
x = 28

See similar equations:

| -3d+8+6d=-13 | | 20x^2+7x-15=0 | | x^2+6y-5z+k=75y-3k+x^3-z | | 2x^2-5x-33=0 | | 3xn=23.4 | | -16t^2+75t=0 | | 7x-7=7x-7 | | 5z-4z+13=11 | | 6x^3-10x^2y-56xy^2=0 | | (x+0)*(x-70)=0 | | 3x^2+2xy-8y^2=0 | | 4m+8m-140=0 | | 2x^2-11xy+5y^2=0 | | 6z+7=0 | | 6n-39=-3 | | 3x+7x-9-x= | | 4(0.2x+0.56)=1.61-2.37x | | 5f-10= | | 4a=5.75 | | 0j=30-4j | | 5f-10=3f+6 | | -60x^2+64x+60=0 | | 197=95-x | | 4(v+3)-7v=6 | | 5(2d+5)=-(9-d) | | -15x^2+16x+1=0 | | -17k=24+13 | | -60x^2+64x+4=64 | | 17k=24+13 | | -60x^2+64x+4=0 | | 2x^2+13x-70=0 | | 157=11-v |

Equations solver categories